2017
DOI: 10.11114/jets.v6i1.2841
|View full text |Cite
|
Sign up to set email alerts
|

Creating Awareness of Sexual Abuse in Children with Special Education Needs: Depending on the Opinions of Teachers of the Mentally Handicapped

Abstract: The purpose of this research is to determine what students and families should do in order to prevent sexual abuse in students who need special education, depending on the opinions of teachers of mentally handicapped students. The qualitative research technique was used in this research. The study population of the research consisted of the teachers of mentally handicapped individuals working in Turkey/Konya province. The study population included 35 teachers. Semi-structure interview method was used as data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…According to Girgin-buyukbayraktar et al, teachers, family members, caregivers, and special education specialists who provide self-care for individuals with intellectual disabilities encounter issues with sexual and intimate relationships involving incorrect societal stereotypes, handicaps in obtaining information, overprotective parenting and a lack of places to meet, inability to control sexual urges, and being unable to control sexual urges [ 30 ]. The results of a study in Kenya revealed that teachers emphasized the need for sex training for adolescents with intellectual disabilities, and teaching basic topics such as sexual relation, intimacy, pregnancy, condom-use and other methods of contraception, prevention of sexual abuse was considered necessary to empower these adolescents [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Girgin-buyukbayraktar et al, teachers, family members, caregivers, and special education specialists who provide self-care for individuals with intellectual disabilities encounter issues with sexual and intimate relationships involving incorrect societal stereotypes, handicaps in obtaining information, overprotective parenting and a lack of places to meet, inability to control sexual urges, and being unable to control sexual urges [ 30 ]. The results of a study in Kenya revealed that teachers emphasized the need for sex training for adolescents with intellectual disabilities, and teaching basic topics such as sexual relation, intimacy, pregnancy, condom-use and other methods of contraception, prevention of sexual abuse was considered necessary to empower these adolescents [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that if schools perform well and provide high-quality sexual training programs for parents, they will be a good place to teach responsible decision-making skills in sexual life and answer the ambiguities of parents to solve their children's sexual problems and by empowering the parents and providing motivation, enable them to guide their adolescent sexually and control risky sexual behaviors [ 32 ]. In this regard, researchers in other studies mentioned that in order to solve sexual problems, individuals with intellectual disabilities, their teachers, and parent should cooperate [ 30 , 33 ]. Therefore, the optimal interaction between school and home is considered one of the most fundamental issues in the country's education system which can perhaps be mentioned as a missing link of education and training.…”
Section: Discussionmentioning
confidence: 99%
“…Bentuk tanggung jawab guru sekolah luar biasa kepada orangtua dalam melakukan pencegahan kekerasan seksual juga sejalan dengan penelitian sebelumnya, bahwa guru harus mampu menggantikan fungsi keluarga dengan selalu memberikan bimbingan dan pengawasan di sekolah (Fitriani et al, 2018). Berdasarkan penelitian berbeda diketahui bahwa anak-anak dengan disabilitas lebih rentan mengalami pelecehan seksual sehingga demi menghindari kejadian tersebut terjadi, para guru harus meningkatkan kesadaran anak, keluarga, dan masyarakat (Büyükbayraktar et al, 2017) yang tinggi dalam menjalani seluruh proses kegiatan, termasuk yang berkaitan dengan kegiatan akademik (Mulyadi et al, 2020). Berdasarkan hasil penelitian ini, dukungan yang didapatkan dalam menjalankan upaya pencegahan kekerasan seksual yaitu dari instansi/komunitas berupa pelatihan kesehatan reproduksi, orangtua, dan sekolah.…”
Section: Pembahasan Aunclassified
“…Öğretmen ve yöneticilerin öğrencilerin çeşitli beceri ve tutumları üzerindeki rolünü ortaya koyan farklı araştırmalar mevcuttur (Büyükkaragöz ve Kesici, 1998;Kesici, 2007;2014;2015;Izgar, Gürsel, Kesici ve Negiş, 2004). Ayrıca özel eğitim öğretmenlerinin engelli öğrencilerine yönelik görüşleri ile ilgili yapılmış çalışmalar da konunun önemine vurgu yapmaktadır (Girgin-Büyükbayraktar, Konuk-Er ve Kesici, 2017a;2017b). Bunun yanı sıra özel eğitim öğretmenlerinin ve öğretmenlerin psikolojik ihtiyaçlarının karşılanması yaşam kaliteleri (Bozgeyikli, 2018) ve stres düzeyleri açısından (Avcı, Bozgeyikli ve Kesici, 2017) Cities that develop rapidly with the technological and industrial changes, started to restructure without a plan and the life is getting difficult in each day for the individuals.…”
Section: Tartışma Ve Sonuçunclassified